2016
DOI: 10.1371/journal.pone.0166145
|View full text |Cite
|
Sign up to set email alerts
|

Co-Circulation of 72bp Duplication Group A and 60bp Duplication Group B Respiratory Syncytial Virus (RSV) Strains in Riyadh, Saudi Arabia during 2014

Abstract: Respiratory syncytial virus (RSV) is an important viral pathogen of acute respiratory tract infection (ARI). Limited data are available on molecular epidemiology of RSV from Saudi Arabia. A total of 130 nasopharyngeal aspirates were collected from children less than 5 years of age with ARI symptoms attending the Emergency Department at King Khalid University Hospital and King Fahad Medical City, Riyadh, Saudi Arabia between October and December, 2014. RSV was identified in the 26% of the hospitalized children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 71 publications
(134 reference statements)
5
49
0
Order By: Relevance
“…A total of 305 samples from ARTI patients, including infants, children and adults, were collected, and 77 (25.2%) of the patients were found to be positive for RSV by multiplex real-time PCR. Our results, which demonstrated the predominance of the RSV-A group over the RSV-B group in the clinical samples, are in agreement with the findings of the majority of the studies on the epidemiology of RSV genotypes [23,[25][26][27][28][29][30]. We found that most of the patients had RSV single infections, while 17 (22%) had mixed infections of RSV and other respiratory viruses.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A total of 305 samples from ARTI patients, including infants, children and adults, were collected, and 77 (25.2%) of the patients were found to be positive for RSV by multiplex real-time PCR. Our results, which demonstrated the predominance of the RSV-A group over the RSV-B group in the clinical samples, are in agreement with the findings of the majority of the studies on the epidemiology of RSV genotypes [23,[25][26][27][28][29][30]. We found that most of the patients had RSV single infections, while 17 (22%) had mixed infections of RSV and other respiratory viruses.…”
Section: Discussionsupporting
confidence: 92%
“…Also, the AN1 genotype was a dominated genotype in India among children < 6 years old during the period 2009-2012 [28] and in Italy among children < 3 years old during 2006-2012 [63]. Moreover, between October and December 2014, NA1 and ON1 genotypes of group A RSV dominated in Riyadh, Saudi Arabia, among children less than five years of age with ARI symptoms [30].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Further genetic analysis of the nucleotide sequence of the second hypervariable region on the G gene allowed for the classification into genotypes within antigenic groups RSV-A and B [9,10]. Many studies have reported the molecular epidemiology and genetic variability of RSV worldwide [10,11,12,13,14,15,16,17,18,19,20], revealing the emergence and spread of new genotypes with duplication of ~60 to 70 nucleotides in this G hypervariable region for RSV-A (RSV Ontario) and RSV-B (RSV Buenos Aires) [15,19,21,22]. Although none of the variants or genotypes has been consistently associated with greater virulence or pathogenicity [13,18,22,23], some recent reports describing clinical aspects of contemporary genotypes (NA1 and ON1) have shown higher frequencies of LRTI and hospitalizations rates [24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Two such remarkable events were the 60-bp duplication in group B RSV in Argentina in 1999 and the 72-bp duplication in group A RSV in Canada in 2011 [45,46] . These new genotypes of RSV with their duplications, known as BA and ON1, respectively, spread to different geographical regions across the globe due to immunologically naive travellers [47][48][49][50] . The mathematics of these spreading events is well known today, and a sophisticated array of computational and mathematical models can be used to accurately back-predict such events.…”
Section: Evolutionary Driversmentioning
confidence: 99%